2020
DOI: 10.1007/s00253-020-10584-1
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the highly expressed small carbohydrate-binding protein Cgt improves the acarbose formation in Actinoplanes sp. SE50/110

Abstract: Actinoplanes sp. SE50/110 (ATCC 31044) is the wild type of industrial producer strains of acarbose. Acarbose has been used since the early 1990s as an inhibitor of intestinal human α-glucosidases in the medical treatment of type II diabetes mellitus. The small secreted protein Cgt, which consists of a single carbohydrate-binding module (CBM) 20-domain, was found to be highly expressed in Actinoplanes sp. SE50/110 in previous studies, but neither its function nor a possible role in the acarbose formation was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(93 reference statements)
1
2
0
Order By: Relevance
“…This effect is supposed to be caused by the reduced metabolic burden, since Cgt was identi ed to be one of the highest abundant proteins in Actinoplanes sp. SE50/110 [87][88][89]. The similar expression patterns shown in this study, support the suggestion, that by deletion of genes co-expressed with the acb gene cluster, the acarbose formation might be improved.…”
Section: Identi Cation Of Genes Co-expressed To the Acb Gene Clustersupporting
confidence: 90%
“…This effect is supposed to be caused by the reduced metabolic burden, since Cgt was identi ed to be one of the highest abundant proteins in Actinoplanes sp. SE50/110 [87][88][89]. The similar expression patterns shown in this study, support the suggestion, that by deletion of genes co-expressed with the acb gene cluster, the acarbose formation might be improved.…”
Section: Identi Cation Of Genes Co-expressed To the Acb Gene Clustersupporting
confidence: 90%
“…Being almost half the size of the Cas9 family of proteins and less toxic as compared to SpCas9 or FnCas12a, we believe that the hypercompact AsCas12j-2 will be a valuable tool in the strategy to generate genomic perturbations in Streptomyces. Previous studies have also shown successful applications of various CRISPR-Cas strategies from Streptomyces to the rare Actinomycetes without modifications or the addition of helper proteins [27][28][29][30][31][32]. In the same manner, we predict that the usage of Cas12j-2 could also be applied across the Actinomycetes family.…”
Section: Discussionsupporting
confidence: 55%
“…The function of the gene product is unclear. Several functional analyses were carried out on the extracellular protein Cgt, but no enzymatic activity could be determined [82]. However, the deletion of cgt lead to an increase of acarbose formation in Actinoplanes sp.…”
Section: Identi Cation Of Genes Co-expressed To the Acb Gene Clustermentioning
confidence: 99%
“…However, the deletion of cgt lead to an increase of acarbose formation in Actinoplanes sp. SE50/110 [82]. This effect is supposed to be caused by the reduced metabolic burden, since Cgt was identi ed to be one of the highest abundant proteins in Actinoplanes sp.…”
Section: Identi Cation Of Genes Co-expressed To the Acb Gene Clustermentioning
confidence: 99%